“A planet made of tears and piles of scrap” (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The text presents issue no. 25 of Móin-Móin Magazine - Studies in the Arts of Puppetry, with the theme Puppetry, Ecology and Sustainability. To do so, it raises concerns that supported the questions launched as a provocation to the authors of this call.
Keywords: Móin-Móin Magazine; Puppetry; ecology; sustainability